Daughters and Sons of Immigrants: The "Second Generations" as an Emerging Element in the Field of Migration Studies in Chile - Jaramillo, Matías (Última Década, 2023)
The field of migration studies in Chile has strengthened throughout the last decades. In parallel, the migration pattern has become more complex and dynamic, bringing new topics up to the table, pushing the different disciplines to produce new objects and, consequently, to broaden their perspectives. Within this context, this article suggests the development of an object of study named “second generations”, i.e., daughters and sons of immigrants born in their mothers and fathers´ new country. In order to do so, the field of migration studies is established, some definitions linked to the Chilean context are given, and two conditioning factors that are linked to their socialization in Chile and to the heritage of migratory condition are proposed.